2017
DOI: 10.1210/js.2017-00283
|View full text |Cite
|
Sign up to set email alerts
|

Harvey Cushing Treated the First Known Patient With Carney Complex

Abstract: Context:Carney complex (CNC) is a syndrome characterized by hyperplasia of endocrine organs and may present with clinical features of Cushing syndrome and acromegaly due to functional adrenal and pituitary gland tumors. CNC has been linked to mutations in the regulatory subunit of protein kinase A type I-alpha (PRKAR1A) gene.Design:Tissue samples were taken from the hypothalamus or thalamus or tumors of patients with pituitary adenomas seen and operated on by neurosurgeon Harvey Cushing between 1913 and 1932. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, we performed similar studies in another patient, not included in this cohort because of age, and found LOH in tissue sample (unpublished information). Penetrance of CNC in PRKAR1A-positive cases is greater than 95% by the age of 50 years but at least two variants have been shown to result in incomplete penetrance (43). Typical CNC-related PAs are somatotroph, mixed GH/PRL-secreting adenomas or corticotropinomas, but PAs are very rarely the first manifestation of the syndrome (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, we performed similar studies in another patient, not included in this cohort because of age, and found LOH in tissue sample (unpublished information). Penetrance of CNC in PRKAR1A-positive cases is greater than 95% by the age of 50 years but at least two variants have been shown to result in incomplete penetrance (43). Typical CNC-related PAs are somatotroph, mixed GH/PRL-secreting adenomas or corticotropinomas, but PAs are very rarely the first manifestation of the syndrome (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, one year after he described bilateral primary pigmented nodular adrenocortical disease (PPNAD) in four young patients with Cushing's syndrome (1), J A Carney, pathologist at the Mayo Clinic, described for the first time the 'complex of myxomas, spotty pigmentation and endocrine overactivity' (2), later named after him, based on a retrospective study of 40 patients. The 'Carney complex' (CNC) was consistent with some cases reported in the literature in the previous 4 years as 'NAME syndrome' (3) or 'LAMB syndrome' (4) (for naevi, atrial myxoma, myxoid neurofibromata and ephelides and lentigines, atrial myxoma, mucocutaneous myxomas and blue naevi, respectively), and probably consistent with a case of fatal bilateral atrial myxomas associated with 'many dark brown to black freckles on the skin, reported in 1960 (5); even evidence has been shown that Harvey Cushing treated the first known patient with Carney complex, more than 70 years before its first description (6).…”
Section: Introductionmentioning
confidence: 64%
“…However, the first (now molecularly confirmed) CNC patient was reported by Professor Harvey Cushing in 1913. The patient presented acromegaly due to pituitary tumour, skin pigmentation and adrenal pathology [ 132 ]. The analysis of archive tissue revealed a PRKAR1A mutation.…”
Section: Germline Mutationsmentioning
confidence: 99%